Reward and punishment sensitivity in shy and non-shy adults: Relations between social and motivated behavior - Hardin, Michael G. (2006)
Few studies have examined underlying mechanisms linking social behavior, motivated behavior, and reward and punishment systems. The current study was designed to investigate these mechanisms by examining responses to both rewarding and punishing non-social stimuli in shy and non-shy adults. Ninety-three participants, comprising three social behavior groups (Shy, Non-shy, Control) completed the Monetary Incentive Delay task. Consistent with previous research, all participants were sensitive to incentive manipulations. There were also significant individual differences in response. Non-shy participants demonstrated sensitivity to both reward and punishment stimuli, and behavior indicative of high levels of arousal in approach motivation. Shy individuals demonstrated a large discrepancy in sensitivity to reward compared to punishment, with this discrepancy being driven by enhanced sensitivity to reward. Their behavior suggested conflict generated by increased arousal in both approach and withdrawal motivation systems. Current findings contribute to theoretical accounts of relations between social behavior and behavior modulated by reward and punishment. These findings carry implications for the study of psychopathology and neuroimaging research designed to examine relationships between social behavior, motivated behavior, and underlying reward and punishment systems.